European Cancer Summit 2022 submission for Digital Health NetworkThe Survivorship Passport: a digital tool for better and homogeneous long-term care for childhood cancer survivors. (March 2023) - Grabow, Desiree; Filbert, Anna-Liesa; Saraceno, Davide; Kremer, Leontien; Skinner, Rod; Hjorth, Lars; Ladenstein, Ruth; Scheinemann, Katrin; Kepak, Tomas; Kepakova, Katerina; Muraca, Monica; Haupt, Riccardo; et al.
Abstract: Background: Many childhood and adolescent cancer survivors (CCS) and their healthcare professionals lack information about possible late effects, personal risk profiles and the need of long-term follow-up care. Most have poor or no access to their clinical and treatment data as well as to a survivorship care plan. The Survivorship Passport (SurPass) is an innovative, digital tool, developed by the PanCare community in previous and on-going EU-funded projects (ENCCA, ExPO-r-Net, PanCareSurFup, PanCareFollowUp, PanCareSurPass), that can be used to overcome these gaps and improve people-centered long-term follow-up care. Methods: Aim of the SurPass and of the PanCare community is to improve the quality of life and health status of CCS and to address their potential needs through the development of successively improving versions and functionalities of the platform. The SurPass provides an electronical and paper-based summary of a CCS´s clinical history, with detailed information about diagnosis and treatment, coupled with personalized follow-up and screening recommendations based on evidence-based guidelines published by the International Guidelines Harmonization Group (IGHG) and the PanCare Guidelines Group. Algorithms built into the platform allow the creation of an individualized care plan. Results: This endeavor started in 2011 when the prototype of the SurPass platform was developed (ENCCA) and integrated the first set of IGHG follow-up recommendations. SurPass was further improved (v1.1) by multi-language translation (ExPO-r-Net), and with a complete set of organ-specific recommendations alongside further new IGHG and PanCare guidelines (PanCareFollowUp v1.2). SurPass v2.0 is currently implemented and spread over several centers in six European countries (PanCareSurPass) whilst testing the interoperability between institutional electronic medical records and the SurPass platform. Similar to Europe's vision of a 'Cancer Survivor Smart Card', the SurPass tool was developed as a 'resource' function to link the individual treatment history to best surveillance and individual follow-up care recommendations for CCS. Conclusions: SurPass can be considered a proof of concept of the clinical-history and personalized-care modules sought under the EU-announced Cancer Survivor Smart Card initiative. Within the newly funded smartCARE project coordinated by ECO, we will share the experiences of the PanCare community with SurPass and international guideline development in survivorship since 2011.